(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS?CoV-2) cases are being frequently reported nowadays and the objective of this clinical case report is to highlight its unique presentation as acute icteric sever hepatitis. Case report: A 28-year-old female patient presented with 3 days history of fever, abdominal pain, nausea, vomiting and jaundice. Lab investigations revealed positive COVID-19 reverse transcription-polymerase chain reaction test along with picture suggestive of acute severe hepatitis (Aspartate aminotransferase; 2772 U/L (N: